Enhancing Saudi EFL Learners’ Speaking and Pronunciation Skills Through Duolingo - AbuSahyon , Alia Sa'ad Eldin; Elsharief , Nadia Ali; Farah , Ena'am Abdelgader (International Journal of Basic and Applied Sciences, 2025)
With the growing global importance of English proficiency, especially in academic and professional domains, improving oral communication skills among English as a Foreign Language (EFL) learners has become a crucial objective in language education. In Saudi Arabia, many university students face challenges in speaking fluently and pronouncing English accurately due to limited exposure to authentic spoken English and communicative practice. Mobile-assisted language learning (MALL) tools like Duolingo, which incorporate gamified and AI-driven elements, offer an innovative solution to supplement traditional classroom methods. This research is important because it exam-ines the effectiveness of the Duolingo app in enhancing the pronunciation and speaking skills of Saudi EFL, specifically, pronunciation accuracy, fluency, stress, and intonation. A quasi-experimental design was employed, involving 130 Saudi EFL students from Najran University who were purposively selected based on their similar English proficiency levels. They were divided into an experimental group using Duolingo and a control group following traditional speaking activities. Quantitative data were collected through pre- and post-tests, while qualitative insights were gathered from student surveys. The findings reveal that the experimental group demonstrated significant improvements in pronunciation and speaking fluency, with statistical significance in phoneme accuracy, stress, and intonation. Furthermore, survey responses indicate a positive perception of Duolingo’s interactive features, with students reporting increased confidence and motivation to practice spoken English. The study highlights the potential of AI-driven mobile applications in supplementing conventional language instruction, offering valuable implications for EFL educators seeking to integrate technology into pronunciation training.